Reinvigorating the WTO as a negotiating forum - Nakagawa, Junji; Akman, Sait; Berger, Axel; Bianchi, Eduardo; Chi, Manjiao; Laborde Debucquet, David (T20, 2019)
The multilateral trading system is on the verge of a crisis arising from, among others, the dysfunction of the WTO as a forum for trade liberalization and trade related rule-making. The G20 should tackle with this challenge in a proactive and innovative manner by reinvigorating the WTO as a forum for negotiation. Possible policy options include multilateral agreements with multi-speed implementation, plurilateral agreements and critical mass agreements, but priority should be on multilateral agreements with multi-lanes. Possible themes for such negotiations can be e-commerce and investment facilitation.